2019
DOI: 10.7150/jca.31539
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative AFU Is a Useful Serological Prognostic Predictor for Colorectal Liver Oligometastasis Patients Undergoing Hepatic Resection

Abstract: Background: Preoperative alpha-l-fucosidase (AFU) has been used as a diagnostic biomarker for several cancers, but its role as a prognostic predictor in colorectal cancer liver oligometastasis (CLOM) patients after radical surgery has not been well defined. This study aimed to investigate the prognostic significance of preoperative serum AFU for CLOM patients after hepatic resection.Methods: A retrospective data set was collected to evaluate the prognostic value of preoperative AFU in CLOM patients after radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…According to previous research, NLN count at the time of lymphadenectomy may have a distinct effect on patient survival (27)(28)(29). Therefore, in the current study, the optimal cutoff value for NLN count was identified using X-tile software, which has been used in other studies (29,30). These results found the optimal cutoff value for NLN count to be 13 in nonmetastatic patients, with patients with a count of 13 or more than 13 at NLN dissection had significantly better CSS than those with less than 13.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, NLN count at the time of lymphadenectomy may have a distinct effect on patient survival (27)(28)(29). Therefore, in the current study, the optimal cutoff value for NLN count was identified using X-tile software, which has been used in other studies (29,30). These results found the optimal cutoff value for NLN count to be 13 in nonmetastatic patients, with patients with a count of 13 or more than 13 at NLN dissection had significantly better CSS than those with less than 13.…”
Section: Discussionmentioning
confidence: 99%
“…Serum tumor markers play important roles in the diagnosis, prognostic prediction and recurrence monitoring of gastrointestinal malignancies. As studies have suggested, AFU was considered to be related to liver metastasis in colorectal cancer [ 4 ]; AFP was associated with prognosis in gastric cancer patients undergoing surgery alone [ 5 ]; preoperative CEA could predict the prognosis of GC patients with no lymph node metastasis [ 6 ]; CA199 was an independent prognostic factor in gastroesophageal junction (GEJ) cancer patients who experienced surgery alone [ 7 ]; the CA125 level was related to the degree of peritoneal dissemination and the existence of malignant ascites in GC patients with peritoneal metastasis [ 8 ]; and CA724 was correlated with pTNM stage in gastric carcinoma patients [ 9 ]. However, for GC patients who underwent NCT, the evidence of these markers is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Serum tumor markers play important roles in the diagnosis, prognostic prediction and recurrence monitoring of gastrointestinal malignancies. As studies have suggested, AFU was considered to be related to liver metastasis in colorectal cancer [4]; AFP was associated with prognosis in gastric cancer patients undergoing surgery alone [5]; preoperative CEA could predict the prognosis of GC patients with no lymph node metastasis [6]; CA199 was an independent prognostic factor in gastroesophageal junction (GEJ) cancer patients who experienced surgery alone [7]; the CA125 level was related to the degree of peritoneal dissemination and the existence of malignant ascites in GC patients with peritoneal metastasis [8]; and CA724 was correlated with pTNM stage in gastric carcinoma patients [9]. However, for GC patients who underwent NCT, the evidence of these markers is still insu cient.…”
Section: Introductionmentioning
confidence: 99%